Pengaruh Pengalaman Dan Citra Destinasi Terhadap Nilai Pelanggan Berimplikasi Terhadap Loyalitas Pengunjung - Syamsul Bahri; Farida Yuliaty; Kosasih Kosasih (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This research aims to determine the direct and indirect influence of experience and destination image on loyalty through customer value in the Ratu Intan tourist area, Amal Beach, Tarakan City, either partially or simultaneously. The sample in this research was 114 visitors to Ratu Intan Amal Beach. The data collection techniques and tools used were observation, interviews, literature and questionnaires. The research results show that the direct influence of experience is not significant on customer value, the direct influence of destination image is significant on customer value, the direct influence of experience is not significant on loyalty, the direct influence of destination image is not significant on loyalty, the direct influence of customer value is significant on loyalty. Indirectly, experience is not significant to loyalty through customer value, indirectly destination image is significant to loyalty through customer value. Simultaneously the experience and image of the destination have a positive and significant effect on customer value, simultaneously the experience and image of the destination have a positive and significant effect on loyalty. Based on this, the management of the Ratu Intan Amal Beach area can evaluate and arrange quality shopping facilities and public facilities so as to give a positive impression to visitors to the Ratu Intan Amal Beach area, Tarakan City.